Practice Patterns and Impact of Postchemotherapy Retroperitoneal Lymph Node Dissection on Testicular Cancer Outcomes - Woldu, Solomon L. (Eur Urol Oncol, 2018)
BACKGROUND: Owing to surgical complexity and controversy regarding indications, there are wide practice variations in the use of postchemotherapy retroperitoneal lymph node dissection (PC-RPLND). OBJECTIVE: To evaluate patterns of PC-RPLND use in the USA and evaluate the association between PC-RPLND and survival in advanced nonseminomatous germ cell tumors (NSGCTs). DESIGN, SETTING, AND PARTICIPANTS: A retrospective, observational study using National Cancer Data Base (NCDB) data from 2004–2014 for 5062 men diagnosed with stage II/III NSGCT. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: In a comparative analysis based on receipt of PC-RPLND, the primary outcome of interest was factors associated with omission of PC-RPLND as explored via logistic regression. As a secondary outcome, we evaluated the association between PC-RPLND and overall survival (OS) via multivariable Cox regression and propensity score matching (PSM). RESULTS AND LIMITATIONS: Patients undergoing PC-RPLND were more likely to be younger, white, privately insured, and reside in more educated/wealthier regions (p < 0.001). Insurance status was independently associated with receipt of PC-RPLND; compared to patients with private insurance, those without insurance were significantly less likely to receive PC-RPLND (odds ratio 0.49; p < 0.001). After multivariate adjustment, age, comorbidity, non-private insurance, distance from hospital, clinical stage, and risk group were independently associated with all-cause mortality. In addition, omission of PC-RPLND remained associated with all-cause mortality (hazard ratio 1.98; p < 0.001). After PSM, the 5-yr OS was significantly lower among those not undergoing PC-RPLND (72% vs 77%; p = 0.007). CONCLUSIONS: PC-RPLND represents a critical part of the multidisciplinary management of NSGCT. Patients with non-private insurance are less likely to undergo PC-RPLND, and omission of PC-RPLND is associated with lower OS. PATIENT SUMMARY: We evaluated the practice patterns for advanced testicular cancer management and found that patients who did not undergo a postchemotherapy retroperitoneal lymph node dissection were more likely to have worse survival outcomes. Patients with unfavorable insurance were less likely to receive this surgical treatment.